Separation of Urban Substation Noise and Environmental Noise based on Independent Component Analysis. Issue 1 (1st February 2023) - Xu, Luwen; Qiu, Ni; Yang, Bo; Peng, Shiwei
Abstract: With the development of urbanization, substations have started to be established in urban areas where the population is concentrated. To realize effective control of the substation noise, accurate measurements of the noise inside the substation and the surrounding area are necessary. However, in an urban area, the background noise, such as traffic noise, causes the sampled signals to contain not only the substation noise but also the background noise, which decreases the measurement accuracy. Thus, separating the substation noise from the environmental background noise is necessary. An independent component analysis method is used to realize the separation of the substation noise from complex environmental noises. In this paper, two typical environmental noises are selected, and their characteristics and the urban substation noise are analyzed. Then, a separation method based on the independent component analysis is constructed for separating substation noise. Its accuracy is evaluated using measured mixed signals. The verification shows that the separated substation noise is very close to the original substation noise signal, which shows that the method can be used in practical substation noise control engineering applications.